CAN THE PRICES OF THE WORLD CRUDE OIL AS A PROXY COST TRANSPORTATION IN TRADE IN ASEAN-3? - Adi, Lumadya (Jurnal Ilmu Ekonomi dan Pembangunan, 2016)
The purpose of this paper is to examine the effect of crude oil prices, GDPimporter, and GDPexporter on trade in three ASEAN includes: Indonesia, Malaysia, and Thailand.Analysis tools are: Ordinary Least Squares (OLS) and the Fixed Effects Model (FEM). In addition to the three countries within ASEAN, researchers include two countries outside ASEAN, namely the USA and Japan. This type of data is the Panel Data with 60 observations.The results of data analysis based on FEM is:For Indonesia: GDPexporter, GDPimporter, and the price of crude oil influence significant and positive on trade. Variations are able to be explained by 85.39%.For Malaysia: GDPexporter, GDPimporter, and the price of crude oil influence significant and positive on trade. Variations are able to be explained by 82.27%.For Thailand: GDPexporter, GDPimporter, and the price of crude oil significant and positive on trade. Variations are able to be explained by 79.74%. Keywords: crude oil prices, GDPexporters, GDPimporters, intra trade